Chemical hazards arising from shale gas extraction - Daria Pakulska (Nofer Institute of Occupational Medicine, 2015)
The development of the shale industry is gaining momentum and hence the analysis of chemical hazards to the environment and health of the local population is extremely timely and important. Chemical hazards are created during the exploitation of all minerals, but in the case of shale gas production, there is much more uncertainty as regards to the effects of new technologies application. American experience suggests the increasing risk of environmental contamination, mainly groundwater. The greatest concern is the incomplete knowledge of the composition of fluids used for fracturing shale rock and unpredictability of long-term effects of hydraulic fracturing for the environment and health of residents. High population density in the old continent causes the problem of chemical hazards which is much larger than in the USA. Despite the growing public discontent data on this subject are limited. First of all, there is no epidemiological studies to assess the relationship between risk factors, such as air and water pollution, and health effects in populations living in close proximity to gas wells. The aim of this article is to identify and discuss existing concepts on the sources of environmental contamination, an indication of the environment elements under pressure and potential health risks arising from shale gas extraction. Med Pr 2015;66(1):99-117